2013
DOI: 10.1007/s00277-013-1918-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage pattern in the patients with factor XIII deficiency

Abstract: Intracranial hemorrhage (ICH) is one of the most severe and life-threatening manifestations occurring in the patients with factor XIII (F XIII) deficiency. The aim of this study was to describe the ICH pattern in the patients suffering from F XIII deficiency. In this case series, we investigated 38 patients with severe F XIII deficiency in south of Iran from January to May 2012. ICH pattern, neurologic complications, efficacy of treatment, and incidence of recurrence were reported. The site of ICH was intrapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…We previously reported this high rate of morbidity and mortality among patients with FXIIID, among whom CNS bleeding (83%) was the most common cause of mortality [8]. Moreover, CNS bleeding in the majority of the affected individuals causes neurologic complications, including locomotor disability, psychological impairment, mental disorders, as well as speech and visual impairment [10]. Another important finding was genetic predisposition to CNS bleeding among our patients with FXIIID.…”
Section: Discussionmentioning
confidence: 91%
“…We previously reported this high rate of morbidity and mortality among patients with FXIIID, among whom CNS bleeding (83%) was the most common cause of mortality [8]. Moreover, CNS bleeding in the majority of the affected individuals causes neurologic complications, including locomotor disability, psychological impairment, mental disorders, as well as speech and visual impairment [10]. Another important finding was genetic predisposition to CNS bleeding among our patients with FXIIID.…”
Section: Discussionmentioning
confidence: 91%
“…When congenital, it presents with severe bleeding, neonatal umbilical bleeding, spontaneous intracranial hemorrhages, poor wound healing, and spontaneous abortions. More commonly, FXIII deficiency is acquired with certain drugs or autoimmune disorders by developing an autoantibody binding to FXIII and interfering with its normal function [1,4]. The results of standard laboratory clotting tests are all normal in FXIII-deficient patients.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, ICH has also been reported to be higher than the normal population in patients with factor X, factor V, factor VII, and factor XIII deficiencies. 17 Khleif et al found the prevalence of neurological diseases including seizure, Parkinson disease, and dementia to be 5%. They also found the prevalence of respiratory diseases, including asthma, to be 11% among these patients.…”
Section: Discussionmentioning
confidence: 99%